Analysis of the genotypebyenvironment interaction of spring barley tested in the Nordic Region of Europe: relationships among stability statistics for grain yield - Nurminiemi, M.; Madsen, S.; Rognli, O.; Bjornstad, A.; Ortíz, R. (Springer, 2002)
Variation in agronomic and quality characteristics was investigated in 220 Nordic spring barley cultivars across distinct environments (6 locations during 3 years) in the Nordic Region of Europe. The objectives of this research were to determine the importance of the genotype by environment interaction in all characteristics evaluated and to establish the relationship among different stability statistics for grain yield. Combined analysis of variance across locations indicated that both environments and genotype by environment interactions influenced significantly the cultivar phenotypes for all characteristics, irrespective of their type (row number) or earliness. The first two interaction principal component axes of the additive-main-effects-and-multiplicative-interaction (AMMI) model accounted together between 35% and 75% of the total genotype-by-environment interaction for all characteristics. Grain yield was, on average, higher in 2-row than in 6-row cultivars, which were significantly earlier in heading and grain maturity than the former. However, in some of the most northern locations, 6-row barley cultivars significantly outyielded on average 2-row barley lines. The genotype by location interaction variance (σ2 GL) accounted by each genotype was significantly associated to the deviation from regression (Tai's λ) while the coefficient of regression (β) was significantly correlated to the IPCA1 and IPCA2 of the AMMI model in 2-row, 6-row and early barley cultivars.